Respuesta :

Answer:

1. [tex] x + 3y = 4x + y [/tex]

2. [tex] y = 9 [/tex]

Step-by-step explanation:

1. x = weight of 1 triangle

y = 1 weight of rectangle

On our left, we have 1 triangle (1x) and (+) 3 rectangles (3y).

This will give us the expression: x + 3y.

On our right, we have 4 triangles (4x) and (+) 1 rectangle (1y).

This will give us 4x + y

herefore, we would have the following:

The equation that represents the hanger would be:

✅[tex] x + 3y = 4x + y [/tex]

2. Substitute x = 6 in [tex] x + 3y = 4x + y [/tex], to find y.

[tex] 6 + 3y = 4(6) + y [/tex]

[tex] 6 + 3y = 24 + y [/tex]

Collect like terms

[tex] 3y - y = 24 - 6 [/tex]

[tex] 2y = 18 [/tex]

Divide both sides by 2

[tex] y = \frac{18}{2} [/tex]

[tex] y = 9 [/tex]

The equation that represent hanger is , 3x-2y = 0

When x = 6 then y will be equal to 9.

From given figure, it is observed that , on right side of hanger 4 triangle and 1 square is present.

And on left side of hanger 3 square and 1 triangle is present.

Since, x represent the weight of one triangle and y represent weight of one square.

Weight of left side of hanger = 3y + x

Weight of right side of hanger = 4x + y

Since, Both side weight are equal.

1. Thus, equation of hanger is,

                   [tex]3y+x=4x+y\\\\3x-2y=0[/tex]

2. When x = 6,

            [tex]3(6)-2y=0\\\\18-2y=0\\\\y=18/2=9[/tex]

Learn more:

https://brainly.com/question/12526075

ACCESS MORE